The Theoretical Description for Chlorantraniliprole Electrochemical Determination, Assisted by Squaraine Dye – Nano-CuS Composite - Volodymyr V. Tkach; Marta V. Kushnir; Silvio Cesar de Oliveira; Hanifa Zh. Salomova; Dilafruz B. Razhabova; Dilfuza M. Musayeva; Laziz N. Niyazov; Yana G. Ivanushko; Mariia P. Mytchenok; Oleksandra V. Ahafonova; Bohdana Y. Banul; Tetiana P. Honchar; et al. (Orbital: The Electronic Journal of Chemistry, 2021)
The theoretical description for the chlorantraniliprole electrochemical determination, assisted by the hybrid composite of squaraine dye with CuS nanoparticles has been described. The correspondent reaction mechanism has been proposed, and the correspondent mathematical model has been developed and analyzed by means of linear stability theory and bifurcation analysis. It has been shown that the chlorantraniprole electrochemical anodical determination on high potential may be efficiently provided by cupper sulfide nanoparticles, stabilized by the squaraine dye. On the other hand, the oscillatory and monotonic instability is also possible, being caused by DEL influences of the electrochemical stage.DOI: http://dx.doi.org/10.17807/orbital.v13i3.1518